2002
DOI: 10.1542/peds.109.6.1131
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor I and Leptin in Umbilical Cord Plasma and Infant Birth Size at Term

Abstract: Levels of IGF-I and leptin in umbilical cord plasma were higher in girls than in boys, but in both sexes, these 2 factors contributed independently and positively to birth weight and length. For IGFBP-1, high levels were associated with low birth weight and reduced length. If intrauterine growth is related to the risk of developing adult diseases, IGF-I, IGFBP-1, and leptin may be involved in the underlying processes.1131-1135 insulin like growth factors, leptin, umbilical cord plasma, birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
2
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 24 publications
9
97
2
5
Order By: Relevance
“…This has been suggested to be a signal of adequate weight gain (20,26). The positive independent correlation of IGF1 with neonatal weight and the lower IGF1 and IGFBP-3 levels in SGA compared with AGA newborns found confirm previous reports by our group (9), and reinforce the postulated role of these peptides in prenatal growth control.…”
Section: Discussionsupporting
confidence: 87%
“…This has been suggested to be a signal of adequate weight gain (20,26). The positive independent correlation of IGF1 with neonatal weight and the lower IGF1 and IGFBP-3 levels in SGA compared with AGA newborns found confirm previous reports by our group (9), and reinforce the postulated role of these peptides in prenatal growth control.…”
Section: Discussionsupporting
confidence: 87%
“…Entre esses hormônios estão: GH fetal, insulina, somatomedina, hormônios tireoidianos e esteróides sexuais 9 . Estudos recentes sugerem que a leptina também esteja envolvida nesse processo [10][11] .…”
Section: Resultsunclassified
“…9 Recent studies have suggested that leptin may also be involved in this process. [10][11] Leptin levels can be measured in the amniotic fluid or in the umbilical cord after the 25th week of gestation. 5 Amniotic fluid leptin reflects the maternal environment, whereas umbilical cord leptin is derived from the placenta or from fetal tissue.…”
Section: Resultsmentioning
confidence: 99%